Effects of Oleo Gum Resin of Ferula assa-foetida L. on Senescence in Human Dermal Fibroblasts - Farshad Homayouni Moghadam; Mehrnaz Mesbah-Ardakani; Mohammad Hossein Nasr-Esfahani (Korean Pharmacopuncture Institute, 2017)
Objectives: Based on data from Chinese and Indian traditional herbal medicines, gum resin of Ferula assa-foetida (sometimes referred to asafetida or asafoetida) has several therapeutic applications. The authors of various studies have claimed that asafetida has cytotoxic, antiulcer, anti-neoplasm, anti-cancer, and anti-oxidative effects. In present study, the anti-aging effect of asafetida on senescent human dermal fibroblasts was evaluated. Methods: Senescence was induced in in vitro cultured human dermal fibroblasts (HDFs) through exposure to H2O2, and the incidence of senescence was recognized by using cytochemical staining for the activity of β-galactosidase. Then, treatment with oleo gum resin of asafetida was started to evaluate its rejuvenating effect. The survival rate of fibroblasts was evaluated by using methyl tetrazolium bromide (MTT) assays. Real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and western blot assays were performed to evaluate the expressions of apoptotic and anti-apoptotic markers. Results: Our experiments show that asafetida in concentrations ranging from 5 × 10-8 to 10-7 g/mL has revitalizing effects on senescent fibroblasts and significantly reduces the β-galactosidase activity in these cells (P < 0.05). Likewise, treatment at these concentrations increases the proliferation rate of normal fibroblasts (P < 0.05). However, at concentrations higher than 5 × 10-7 g/mL, asafetida is toxic for cells and induces cell death. Conclusion: The results of this study indicate that asafetida at low concentrations has a rejuvenating effect on senescent fibroblasts whereas at higher concentrations, it has the opposite effect of facilitating cellular apoptosis and death.